Dokumen kontrak : supply, delivery, installation, testing, commissioning and training of fire fighting services installation for chemical engineering pilot plant for the Faculty of Chemical and Natural Resources Engineering - Universiti Teknologi Malaysia. Biro Inovasi dan Perundingan; Energie Consulting Heidelbergh GMBH (Skudai : Universiti Teknologi Malaysia, 1999)
03